EFEKTIVITAS PENGELOLAAN PIUTANG UNTUK MENINGKATKAN LABA PADA CV. GARUDA PERKASA HONDA MOTOR SIBOLGA - Dwi Indah Rahayu Pasaribu; Safriadi Pohan; Yenni Sofiana Tambunan (Jurnal Ekonomi Bisnis dan Akuntansi, 2022)
This research takes the title of the Effectiveness of Receivables Management to Increase Company Profits. The need to look for cash and credit sales on the influence of receivables that generate profits in the company. The aim of the research is to know the accounts receivable management policy implemented by the company as well as to know the effective management of accounts receivable and to find out what are the obstacles faced by companies in managing receivables. The type of research used is descriptive research with a case study approach. This research takes place at CV. Garuda Mighty Honda Motor Sibolga. which is on Jalan R. Junjungan Lubis No. 1-3 Sibolga City District. Data collection techniques are carried out by collecting methods through interviews and documentation. Analysis of the data used in this study by performing calculations in accordance with the existing problems. The results showed that the company's credit sales have increased significantly in the last five years, and the collection of accounts receivable has accelerated so that the collection results can be rotated by the company according to needs. . The existence of effective accounts receivable management is able to make the company earn more profits from year to year. Suggestions are that the company is expected to be better at collecting receivables and management is expected to be able to provide discounts on credit sales. Discounts that can be given by the company are in the form of installment discounts if the customer pays off sooner than the time period agreed by both parties. In addition, it is hoped that the results of the research will serve as a guideline for further researchers to develop this research to develop the results of the problems that have been discussed.